HOST ROCK AND MINERALIZED ORES GEOCHEMISTRY OF ARINEM VEIN, ARINEM DEPOSIT, WEST JAVA – INDONESIA - Yuningsih, Euis Tintin (Bulletin of Scientific Contribution, 2016)
Geochemically, the major, minor and trace elements play an important role in the various geological processes. The REE characteristics of quartz vein formed during main mineralization stage are representative of mineralization hydrothermal fluid REE compositions. The research concern the integrating geochemistry and mineralogy analyses. It is an ideal method to study the occurrence of gold deposits in the Arinem area. This area is located on the Java island as a part of West Java province of Indonesia. Detail exploration, including some drilling activities, is ongoing to define the gold and base metal reserve as well as the deposit characteristics. Thirty samples from different stage of mineralized body of Arinem vein, altered host rock from different core level, outcrop host rock, Miocene and Pliocene intrusions were analyses for its geochemical composition by using the Induced Couple Plasma (ICP) and Induced Couple Plasma Mass Spectrometer (ICP-MS). Emission Spectrometry was used to extend the lower detection limits and provide a broader spectrum of elements at the Acme Analytical Labortories, Canada.  The REE distribution in the altered host rock of the Arinem deposit indicated that the ΣREE enrichment in the altered host rock, with decreasing in its content from the host rock to the mineralized vein. The observed variations in mineralogy and mineral proportions indicate that Au and Ag came into being only during stage II (except for electrum also indicated at stage I), but that sphalerite, galena, pyrite, chalcopyrite and arsenopyrite were deposited during stages I and II. Keywords : altered host rock, Arinem vein, Geochemistry, Mineralized body, REE. Secara geokimia unsur-unsur utama, sedikit dan jejak (trace) memainkan peran penting dalam beragam proses geologi. Karakteristik unsur tanah jarang (Rare Earth Elements) dalam urat kuarsa yang terbentuk selama tahap mineralisasi utama merupakan representasi dari komposisi REE fluida hidrotermal. Pendekatan yang diterapkan dalam meneliti hal tersebut meliputi integrasi analisis geokimia dan mineralogi, yang merupakan suatu metode yang cukup ideal untuk mempelajari terjadinya deposit emas di Arinem. Daerah Arinem terletak di wilayah Jawa Barat bagian selatan, Indonesia. Eksplorasi detil, termasuk aktifitas pengeboran, sedang berlangsung untuk menentukan cadangan emas dan logam dasar serta karakteristik deposit. Dalam penelitian ini, tiga puluh sampel telah diambil dari tubuh vein Arinem dengan beragam tahapan mineralisasi dan dari batuan induk terubah dengan tingkatan yang berbeda dari inti ke arah luar, serta dari singkapan batuan induk, dan intrusi berumur Miosen dan Pliosen. Analisis untuk mengetahui komposisi kimia menggunakan Induced Couple Plasma (ICP) dan Induced Couple Plasma Mass Spectrometer (ICP-MS). Emission spectrometry digunakan untuk meningkatkan batas bawah deteksi dan memberikan spektrum unsur yang lebih luas. Seluruh analisis tersebut dilakukan di laboratorium “the Acme Analytical Labortories”, Canada. Distribusi REE pada batuan induk terubah dari deposit Arinem mengindikasikan bahwa terjadi pengayaan jumlah REE dalam batuan tersebut, sebaliknya terjadi penurunan kandungannya pada batuan induk yang mengalami mineralisasi vein. Hasil pengamatan menunjukkan bahwa proporsi mineral dan variasi mineraloginya mengindikasikan bahwa kehadiran Au dan Ag hanya terjadi pada tahap II (kecuali untuk elektrum juga diindikasikan pada tahap I). Sebaliknya sfalerit, galena, pirit, kalkopirit dan arsenopirit terbentuk selama tahap I dan II. Kata kunci: batuan induk terubah, vein Arinem, geokimia, tubuh termineralisasi, REE.